The Influence of Digital Games Based Learning on Students’ Learning Outcomes and Motivation - Rahmat Yusny (IAIN Salatiga, 2013)
There is no doubt that the emergence of today's digital age greatly affects the human life - including students in their educational life. In order to simplify the process of studying languages, especially English, many scientists and experts continue to find new and innovative methods. One of them is the method of Digital Games Based Learning (DGBL). However, the implementation effort of DGBL method to improve English language skills of students is still a matter of controversy. It is mainly caused by the use of game - which is assumed by the public just as merely means of entertainment rather than as a medium of learning. Judging on this reason, researchers are interested highlighting them to be their research. This research was conducted in order to view the significance and influence of DGBL in improving English language skills of students - particularly the ability to hear and read - as well as their motivation to learn. The study was conducted over five sessions in March 2013 with a sample of 13 students were selected at random stratification of 68 second -year student population PBI , Ar - Raniry UIN .Researchers collected data by applying the experimental use of games in the classroom , provide pre-test and post-test , as well as distributing questionnaires dealing with motivation. From the analysis of quantitative data, it can be concluded that the method of Digital Games Based Learning (DGBL) can be used to improve student’s achievement and learning motivation in learning English.keywords: Digital Games Based Learning (DGBL) ; Learning outcome ; Motivation